The Factors Associated with Choking Prevention Behavior in Mothers of Toddlers - Yonia Rafika Nanda; Erna Dwi Wahyuni; Praba Diyan Rachmawati (Universitas Airlangga, 2022)
Introduction: Choking is a common health problem in children, especially those under the age of three and younger. Also, one of the most common case in emergency medical service. The purpose of this study was to analyze factors that correlated with choking prevention behaviour in mothers who have toddlers. Methods: This study used a descriptive correlational design with a cross-sectional approach that conducted at an integrated service post, Purworejo Village. The population in this study were 154 mothers who had toddlers. Inclusion criteria include could access google forms, were domiciled in Purworejo Village, and lived with their families and toddlers. Exclusion criteria were mothers with special needs and toddlers with special conditions, and when the research was conducted, the mother was outside the Purworejo village. Sample selection used the cluster sampling technique with the sample size was 111 mothers. Result: There was a relationship between knowledge (p=0.007 r=0.253), attitudes (p=0.018 r=0.224), and family support (p=0.011 r=0.242) with choking prevention behaviour, and there was no relationship between the availability of health facilities (p=0.827 r=0.021) with choking prevention behaviour. Conclusion : Better knowledge, attitudes and family support will represent better choking prevention behaviour. Therefore, support from various parties, such as nurses, is needed to carry out health promotion related to preventing choking in families. Further research is needed regarding other factors influencing mothers' choking prevention behaviour.